2022
DOI: 10.3390/idr14020024
|View full text |Cite
|
Sign up to set email alerts
|

Acute Stroke Care during COVID-19: National Data

Abstract: (1) Background: The pandemic of COVID-19 and subsequent lockdown strategies had a profound impact on many aspects of everyday life. During this time the world faced the unprecedented crisis of healthcare disrupting timely care delivery. This study was designed to evaluate the impact of the pandemic on the acute treatment of stroke in Poland. (2) Methods: The national data on hospitalizations with stroke as a primary diagnosis were obtained from the National Health Fund of Poland. Poisson regression was used to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 24 publications
(25 reference statements)
0
4
0
2
Order By: Relevance
“…The epidemiology of other neurologic conditions, such as stroke, were also affected. During the COVID-19 period, the overall number of hospitalizations due to stroke in Poland dropped by 8.28% compared with the corresponding period of 2019 [ 26 ]. Other authors reported similar findings, with the highest drop of 39.52% during the critical period recorded in Spain [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…The epidemiology of other neurologic conditions, such as stroke, were also affected. During the COVID-19 period, the overall number of hospitalizations due to stroke in Poland dropped by 8.28% compared with the corresponding period of 2019 [ 26 ]. Other authors reported similar findings, with the highest drop of 39.52% during the critical period recorded in Spain [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Decreased admission numbers to stroke units have been reported in multiple countries and institutions. [6][7][8] Regarding reperfusion therapy for AIS, the number of patients with IVT 7) or MT 9) has been reported to have decreased. One of the biggest concerns of the COVID-19 pandemic is its adverse effect on in-hospital time indicators such as DTN, DTP, and DTR.…”
Section: Concerns In Reperfusion Therapy Raised By the Covid-19 Pandemicmentioning
confidence: 99%
“…Spośród odnalezionych badań 10 prac dotyczy diagnostyki i/lub leczenia chorób układu krążenia [30][31][32][33][34][35][36][37][38][39]. Ich zakres jest różnorodny.…”
Section: Badania Dotyczące Leczenia Chorób Układu Krążeniaunclassified
“…W pracy tej wykazano jednak, że liczba zabiegów elektroterapii serca i procedur elektrofizjologicznych spadła istotnie w kwietniu 2020 roku, co nadrobiono w kolejnych miesiącach tego roku [31]. Inne badania potwierdzają te wyniki, wskazując kwiecień 2020 roku jako okres o największym ograniczeniu liczby wykonywanych świadczeń zdrowotnych [35]. W odnalezionych badaniach wskazuje się również na konieczność oceny długoterminowych konsekwencji pandemii COVID-19 [37] (tab.…”
Section: Badania Dotyczące Leczenia Chorób Układu Krążeniaunclassified